Transcriptome profiling of faba bean (Vicia faba L.) drought-tolerant variety hassawi-2 under drought stress using RNA sequencing - Muhammad Altaf Khan; Salem S. Alghamdi; Megahed H. Ammar; Qiwei Sun; Fei Teng; Hussein M. Migdadi; Sulieman A. Al-Faifi (Electronic Journal of Biotechnology, 2019)
Background: Drought is the major factor that limits faba bean (Vicia faba L.) production worldwide. To decipher the molecular basis of drought stress response, we carried out transcriptome profiling of the drought-tolerant genotype of faba bean (Vicia faba L.), Hassawi-2, under drought stress conditions using RNA sequencing. Results: De novo assembly of a total of 606.35 M high-quality pair-end clean reads yielded 164,679 unigenes of leaf tissues. A total of 35,143 (12,805 upregulated and 22,338 downregulated unigenes) and 28,892 (16,247 upregulated and 12,645 down-regulated) genes were differentially expressed under drought stress conditions in the vegetative and flowering stages, respectively. According to the GO and KEGG databases, both the vegetative and flowering stages regulated energy metabolism, transmembrane transporter activity, and secondary metabolites. A total of 538 (272 upregulated and 266 downregulated) and 642 (300 upregulated and 342 downregulated) putative transcription factors in the vegetative and flowering stages, respectively, were identified and classified under different transcription factor families. In addition, a substantial proportion of DEGs identified here were novel, as they could not be mapped to any functional database, therefore suggesting a specific response to drought stress in faba bean. The RNA-seq results were also validated by quantitative reverse-transcription PCR analysis. Conclusion: The transcriptome data generated here using RNA sequencing is the first report of faba bean under drought stress indicating the genes involved in drought tolerance. This information can be used to improve drought tolerance in elite faba bean cultivars and to develop tolerant germplasm for other legume crops.How to cite: Khan MA, Alghamdi SS, Ammar MH, et al. Transcriptome profiling of faba bean (Vicia faba L.) drought-tolerant variety hassawi-2 under drought stress using RNA sequencing. Electron J Biotechnol 2019;39. https://doi.org/10.1016/j.ejbt.2019.02.004. Keywords: Annotations, Differentially expressed genes, Drought stress, Faba bean, Flowering stage, RNA Seq, RNA sequencing, Transcriptome profiling, Unigenes, Vegetative stage, Vicia faba L